Kata Penyukat dalam Bahasa Madura dan Keparalelan-Nya Dalam Morfologi - Rizal Afandi; Qurratul Aini (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan bahasa dan Sastra, 2024)
Madurese has the same words as other languages. The word suffocation in a language has different characteristics from other languages, and also has its own variations in its use. This article aims to find out what types of words in Madurese are and how to use them. This research uses a descriptive qualitative method which consists of three stages, namely the stage of providing data, analyzing data, and also presenting the results of data analysis, thus producing types of words in Madurese. The first is the word animal lover, its use is only specific to animals, such as: jhudhu, tide, etc. Secondly, there is the word plant protector, its use is specific to plant species, for example: kèjhang, tondun, kerreng, ghundung, etc. And the third is the word insulator for inanimate objects, which includes the words insulator in size, the words insulator in container, and the words insulator in action. The use of the word insulator for each type is different, depending on the object being addressed, whether animate or inanimate.